1995
DOI: 10.1254/jjp.69.351
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Inhibitory Effects of Serotonin (5-HT)3-Receptor Antagonists, YM060 and YM114 (KAE-393), on the von Bezold-Jarisch Reflex Induced by 2-Methyl-5-HT, Veratridine and Electrical Stimulation of Vagus Nerves in Anesthetized Rats

Abstract: BJR were largely consistent with those against 5-HT-induced BJR. In contrast, higher doses (100 pg/kg, i.v.) of YM060, YM114, ondansetron and granisetron did not inhibit veratridine (150 pg/kg, i.v.)-induced BJR. Atropine (300 pg/kg, i.v.) abolished bradycardia induced by electrical stimulation of vagal efferent nerves, whereas YM060, YM 114, ondansetron and granisetron had no effect at a dose of 1000 ug/kg, i.v. 5-HT (0.625-5.0 pg) injected into the left ventricle also caused a dose-dependent decrease in hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 17 publications
0
22
0
1
Order By: Relevance
“…In our study, although there was no significant difference in the composite cardiac outcome, the incidence of intraoperative hypotension was lower in the palonosetron exposure group than the nonexposure group. This unexpected effect of palonosetron may be explained by inhibition of the Bezold–Jarisch reflex, which is a cardioinhibitory reflex, including bradycardia, hypotension, and peripheral vasodilation, for which 5‐HT (serotonin) is an important inducing factor via 5‐HT 3 receptors in the intracardiac vagal nerve endings in the setting of decreased blood volume . In previous clinical studies, ondansetron was shown to reduce spinal‐induced hypotension in patients undergoing spinal anesthesia, and granisetron, as another first‐generation 5‐HT 3 receptor antagonist, prevented neural‐mediated hypotension in patients undergoing head‐upright tilt testing .…”
Section: Resultsmentioning
confidence: 98%
“…In our study, although there was no significant difference in the composite cardiac outcome, the incidence of intraoperative hypotension was lower in the palonosetron exposure group than the nonexposure group. This unexpected effect of palonosetron may be explained by inhibition of the Bezold–Jarisch reflex, which is a cardioinhibitory reflex, including bradycardia, hypotension, and peripheral vasodilation, for which 5‐HT (serotonin) is an important inducing factor via 5‐HT 3 receptors in the intracardiac vagal nerve endings in the setting of decreased blood volume . In previous clinical studies, ondansetron was shown to reduce spinal‐induced hypotension in patients undergoing spinal anesthesia, and granisetron, as another first‐generation 5‐HT 3 receptor antagonist, prevented neural‐mediated hypotension in patients undergoing head‐upright tilt testing .…”
Section: Resultsmentioning
confidence: 98%
“…Blockade of the 5-HT3 receptor antagonizes the BJR induced by serotonin. 8,9 White et al observed that i.v. administration of the 5-HT3 antagonist granisetron 50 lg/kg was efficacious in suppressing bradycardia and hypotension associated with the BJR in a rabbit model.…”
Section: Discussionmentioning
confidence: 99%
“…3 Owczuk et al observed that intravenous ondansetron attenuated spinal-induced hypotension. 4 Animal studies suggest that 5-HT (serotonin) may be an important factor associated inducing the BJR in the setting of decreased blood volume [5][6][7][8] ; this effect can be blocked at the 5-HT3 receptor. 9 We hypothesized that spinal-induced hypotension and bradycardia could be minimized with the use of intravenous ondansetron, a 5-HT3 receptor antagonist, in non-labouring obstetric patients undergoing caesarean section.…”
Section: Introductionmentioning
confidence: 99%
“…Ramosetron hydrochloride (ramosetron) is a potent and selective synthetic 5-HT 3 receptor antagonist [4, 5]. The results of animal studies have shown that ramosetron inhibited an acceleration of defecation or diarrhea induced by restraint stress [6].…”
Section: Introductionmentioning
confidence: 99%